Optical and Structural Study of ZnO Thin Films Deposited by RF Magnetron Sputtering at Different Thicknesses: a Comparison with Single Crystal - Jazmati,Abdul Kader (2018)
Optical characterizations of preferred orientation (002) ZnO thin films, prepared by RF magnetron sputtering under pure argon plasma, with different thicknesses have been investigated, where grain size and resistivity increase with thickness. Energy band gap and refractive indices have been calculated. A correlation between band gap values and crystalline quality, which is improved with thickness, has been discussed. The calculated refractive indices of the thicker deposited films have increased as the thickness increases. Full width Half Maxima (FWHM) of band gap Photoluminescence (PL) emission decreases with thickness increasement due to quality improvement as it has been monitored by X-Ray Diffraction (XRD). A comparison between PL spectra of 1200 nm film and ZnO single crystal at low temperature is found to be similar.